1971
DOI: 10.1007/bf00387631
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome-mediated bud development in Pisum sativum

Abstract: Light-grown dwarf peas were disbudded except for a single lateral bud, then transferred to darkness at 24° C. During the dark period the seedlings were irradiated daily for 5 or 7 min with R or FR. The buds exposed to R developed into shoots faster than those irradiated with FR. The R effect was FR reversible, and the FR effect was R reversible. The Pfr form of phytochrome thus promoted shoot growth including cell division, DNA and RNA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…that received 5 min of FR2 irradiation after a 16-h light period from white fluorescent tubes showed almost complete suppression of branching compared to control plants that branched profusely (13). Similar responses were obtained in decapitated Pisum sativum L. seedlings (6) and Nicotiana tabacum L. plants (5), among other species studied.…”
supporting
confidence: 75%
“…that received 5 min of FR2 irradiation after a 16-h light period from white fluorescent tubes showed almost complete suppression of branching compared to control plants that branched profusely (13). Similar responses were obtained in decapitated Pisum sativum L. seedlings (6) and Nicotiana tabacum L. plants (5), among other species studied.…”
supporting
confidence: 75%
“…Some investigators claim promotive effects, others inhibitory. Khudairi (1968) showed promotive effects on buds and seed germination in the presence of red light. Ascorbic acid could be inhibitory to root growth (Khudairi, unpublished data).…”
Section: Discussionmentioning
confidence: 95%
“…Toyoda (1970) also found more ascorbic acid in the plumule of Indian lotus in the light than seedlings grown in the dark. Khudairi et al (1971) found that red light induced bud development in light-grown pea seedlings, and that the red effect is far-red reversible. They also showed that there is more cell division, RNA and DNA in buds exposed to a few minutes of red light.…”
Section: Discussionmentioning
confidence: 97%